A comprehensive study on recycled and virgin PET melt-spun fibers modified by PMDA chain extender. (December 2021) - Qu, Muchao; Lu, Dong; Deng, Hongyi; Wu, Qiang; Han, Lei; Xie, Zixin; Qin, Yijing; Schubert, Dirk W.
Abstract: The effect of chain extender Pyromellitic dianhydride (PMDA) on the comprehensive properties of the virgin (vPET) and recycled Polyethylene terephthalate (rPET) fibers was investigated. Five different weight fractions of PMDA were melt mixed with PETs to create long-chain branched (LCB) structures. The modified LCB-PET granules were melt spun into fibers using a capillary rheometer at 270 and 280 °C, and then aerodynamically stretched by an aspirator at seven take-up pressures. The different shear viscosity, thermal properties and spinnability of LCB-vPET and LCB-rPET, and the surface morphology, draw ratios, tenacity, elongation at break of PET fibers, as well as the performance-reliability plots using Weibull distribution were well discussed. A semi-empirical mathematical model further confirmed the exponential relationship between the tenacity and elongation at break of the PET fibers. This research depicts a visible window for academic and industrial researchers to produce PMDA modified PET fibers with desirable comprehensive properties. Highlights: Comprehensive research on LCB-rPET and LCB-vPET modified by PMDA chain extender. Co-polymer bottle-grade rPET is sensitive to temperature with great spinnability. PMDA enhances tenacity of homo-polymer fiber-grade vPET much compared to rPET. Performance-reliability plot via Weibull distribution for industrial application. Mathematical model revealing the performance level between rPET and vPET fibers.